Pengaruh Reputasi Bank dan Etika karyawan Terhadap Loyalitas Nasabah - Alwahidin, Alwahidin; Wahid Mongkito, Abdul; Ahmad, Ahmad (MADINAH, 2021)
This study aims to determine the effect of bank reputation and employee ethics on customer loyalty (a case study of BTN Syariah KCPS Kendari bank customers) partially and simultaneously. Source of data used in this study is the primary data questionnaire. This study uses a quantitative method because it aims to confirm the data obtained in the field with the existing theory. Samples were obtained by 97 customer respondents at BTN Syariah. Meanwhile, the data collection technique was carried out using the questionnaire method, and literature study. Data were processed using reliability, validity, classical assumptions, multiple linear regression tests, hypothesis testing and coefficient of determination tests using the IBM SPSS 26 for windows program. The results of the data processing indicate that the bank's reputation partially has a significant effect on the customer loyalty variable as indicated by the large t test value of 5.430 > 1.98552. Employee ethics partially has a positive and significant effect on customer loyalty of 3.297 > 1.98552. The results of the t test show that the variables of bank reputation and employee ethics are variables that affect customer loyalty at Bank BTN Syariah. while for the f test the results of bank reputation variables and employee ethics have a joint effect on customer loyalty.